A semi analytic iterative method for solving two forms of blasius equation / Mat Salim Selamat, Nurul Atkah Halmi and Nur Azyyati Ayob - Selamat, Mat Salim; Halmi, Nurul Atkah; Ayob, Nur Azyyati (Universiti Teknologi MARA, Negeri Sembilan, 2019)
In this paper, a semi analytic iterative method (SAIM) is presented for solving two forms of Blasius equation. Blasius equation is a third order nonlinear ordinary differential equation in the problem of the two-dimensional laminar viscous flow over half-infinite domain. In this scheme, the first solution which is in a form of convergent series solution is combined with Padé approximants to handle the boundary condition at infinity. Comparison the results obtained by SAIM with those obtained by other method such as variational iteration method and differential transform method revealed the effectiveness of the SAIM.